Possibility of using fingerprint powders for development of old fingerprints - Muhammad Yusof Omar; Ellsworth, Laura (Universiti Kebangsaan Malaysia, 2012)
The use of conventional fingerprint powder is the easiest and fastest method for fingerprint development. It is also the workhorse at the crime scene and an important method used in the laboratory. The objective of this study was to examine the difference in physical characteristics of the fingerprint after development using different fingerprint powders within a six-week period. The study compared the number of positives identifications of each ‘minutiae’ after application of black fingerprint powder and black magnetic fingerprint powder. The latent fingerprints from the donor were deposited on clean microscope slides. The following prints were applied after thirty minutes. Similar rules of pressure and length of deposition were made as much as possible. The slides were analyzed every week at similar intervals for six continuous weeks with black fingerprint powder and black magnetic fingerprint powder with specific indicator. The black fingerprint powder can be used for three weeks while black magnetic powder can up to fourth weeks. The results gave information on an effective time frame using both fingerprint powders for fingerprint development.